Immunomodulation resulting of helminth infection could be an opportunity for immunization against tuberculosis and mucosal pathogens - Kai Ling Chin; Luis Fonte; Boon Huat Lim; Maria E. Sarmiento; Armando Acosta (Frontiers, 2023)
Approximately, 10 million new tuberculosis (TB) cases were reported in 2020, of which 12% were among children (1). It is estimated that one-quarter of the world population (around 2 billion) is latently infected by Mycobacterium tuberculosis (Mtb) and 5-10% of these individuals will develop active TB (ATB) (1). Infections caused by soil-transmitted helminths (STH) and schistosomes affect about 1.5 billion and 250 million people, respectively, worldwide (2). Children and pregnant women are the population groups with the highest risk of infection by those parasites (3).